Cesarean section in Ethiopia: prevalence and sociodemographic characteristics. (3rd April 2019) - Yisma, Engida; Smithers, Lisa G.; Lynch, John W.; Mol, Ben W.
Abstract: Objective: The objective of this study was to assess the prevalence and sociodemographic characteristics of cesarean section in Ethiopia. Methods: We used data collected for Ethiopia Demographic and Health Surveys (DHS) conducted in 2000, 2005, 2011, and 2016. A two-stage, stratified, clustered random sampling design was used to gather information from women who gave birth within the 5-year period before each of the surveys. We analyzed the data to identify sociodemographic characteristics associated with cesarean section using log-Poisson regression models. Results: The national cesarean section rate increased from 0.7% in 2000 to 1.9% in 2016, with increases across seven of the eleven administrative regions of Ethiopia. Addis Ababa had the highest cesarean section rate (21.4%) in 2016 and the greatest increase since 2000. In the adjusted analysis, women who gave birth in private health facility had a 78.0% higher risk of cesarean section (adjusted prevalence ratio (aPR) (95% CI) 1.78 (1.22, 2.58)) compared with women who gave birth in public health facility. Having four or more births was associated with a lower risk of cesarean section compared with first births (aPR (95% CI) 0.36 (0.16, 0.79)). Conclusions: The Ethiopian national cesarean section rate is about 2%, but the rate varies widely among administrative regions, suggesting unequal access. Cesarean sections were highest among urban mothers, first births, births to women with higher education, and births to women from the richest quintile of household wealth.